GENDER INEQUALITY ANALYSIS OF THE MAIN FEMALE CHARACTER IN NIKI CARO’S MULAN MOVIE: A FEMINISM STUDY - Afina Mirrah Hasna; Endang Yuliani Rahayu (Dinamika Bahasa dan Budaya, 2022)
This research is focused on feminist studies. It is further discussing gender inequality reflected in Mulan, the impact of gender inequality in Mulan and Mulan's efforts to realize gender equality. This research is based on the theory of sexual politics by Kate Millett which explains that women must be able to have masculine and feminine behavior by fighting for gender equality. This means that women must also play the role of men. On the other hand, women can only serve their husbands and raise children when they are only seen as weak figures are called sexual politics. The data of this research is taken from Mulan movie, especially from the movie script and the point of view of the female character. In chapter IV the gender inequality reflected in Mulan, the impact of gender inequality in Mulan and the efforts made to achieve gender equality are discussed referring to Kate Millett theory. The study results that this film is about gender inequality because women are considered weaker and cannot do men's work. In addition, the authors hope that research on women's struggles in the future, especially gender equality, can be carried out more often. Keywords: Gender Inequality, Gender Equality, Feminism Study, Sexual Politics, Mulan Movie